PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL KABUPATEN ROTE NDAO UNTUK MENINGKATKAN LITERASI - Manafe, Jacqulien Eng Jasmine Josiana; Bulu, Vera Rosalina; Ratu, Kurniayu Triastuti R.A. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a picture storybook based on the local wisdom of Rote Ndao Regency that is valid, practical, and effective in improving the reading literacy skills of third-grade elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included 23 students in the limited trial and 46 students in the large-scale trial, consisting of 23 students in the experimental class and 23 students in the control class at UPTD SD Inpres Oesapa Kecil 1. Data were collected through expert validation sheets, teacher and student response questionnaires, and pretest-posttest tests. The data were analyzed using descriptive quantitative analysis, an independent sample t-test, and the N-Gain test to determine the improvement in students' reading literacy skills. The results showed that the developed picture storybook obtained validation scores of 95.83% from material experts, 89.06% from media experts, and 93.47% from language experts, indicating that the product was highly valid. The hypothesis testing revealed a significance value of 0.001 (< 0.05), indicating a significant difference between the experimental and control groups. Furthermore, the average N-Gain score of the experimental group was 0.49, which fell into the moderate category, while the control group obtained an average N-Gain score of 0.21, categorized as low. Therefore, the picture storybook based on the local wisdom of Rote Ndao Regency was considered valid, practical, and effective in improving the reading literacy skills of third-grade elementary school students